Relationship of the Special Wrestling Fitness Test with Aerobic Performance [Relação Do Special Wrestling Fitness Test Com O Rendimento Aeróbio] [Relación del Special Wrestling Fitness Test Con el Rendimiento Aeróbico] - Cofre-Bolados, C; Herrera-Valenzuela, T (Centro Andaluz de Medicina del Deporte, 2021)
Objective: This study investigated the relationship of aerobic physiological variables of the Special Wrestling Fitness Test with the physiological variables measured in an incremental running test. Methods: Eight cadet and junior athletes (male: 2; female: 6) of Olympic freestyle wrestling carried out the Special Wrestling Fitness Test, determining the number of throws, the test index and the peak oxygen consumption, heart rate, respiratory quotient and oxygen pulse. Additionally, the athletes performed a treadmill incremental test to determine the peak oxygen consumption, heart rate, respiratory quotient and oxygen pulse. Pearson s correlation coefficient (p <0.05) was used to establish the relationship between variables. Results: A positive correlation was found between the final heart rate in the Special Wrestling Fitness Test and heart rate peak during the incremental test (r = 0.90; P = 0.002; 95%CI = 0.54-0.98), between heart rate during the Special Wrestling Fitness Test and heart rate peak during the incremental test (r = 0.81; P = 0.002; 95%CI = 0.53-0.98), and between oxygen consumption peak during the Special Wrestling Fitness Test and oxygen consumption peak during the incremental test (r = 0.93; P = 0.001; 95%IC = 0.67-0.99). Conclusions: Physiological variables during the Special Wrestling Fitness Test are related to physiological response during an incremental test. Therefore, trainers could apply the Special Wrestling Fitness Test to monitor changes in aerobic performance as a result of training. © 2021 Consejería de Educación y Deporte de la Junta de Andalucía. Este es un artículo Open Access bajo la licencia CC BY-NC-ND (http://creativecommons.org/licenses/by-nc-nd/4.0/)
Keywords: Combat sports; Evaluation; High-intensity intermittent exercise; Test